ANALYSIS OF CHEMICAL CHARACTERISTICS OF KOMBUCHA TEA SEAWEED Eucheuma cottonii - Rachmawati, Nandya Fitri; Miratis S., Siti Tsaniyatul; Adharani, Nadya; Yulianto, Maqsfiranda Erza Devi; Maulidha, Asih (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2023)
Seaweed is a marine plant that is found in many Indonesian waters. Seaweed has various types, one of which is Eucheuma cottonii seaweed.  So far, Eucheuma cottonii is only used as functional food in the food sector, but there are still few who use it as a functional drink. The purpose of this study was to determine the chemical characteristics of kombucha tea seaweed Eucheuma cottonii. The research method used is experimental. The results of the chemical characteristics obtained in the best treatment are treatment D (12%) with a total sugar content value of 7.67%, total ash content of 0.773%, polyphenol content of 0.177% and tannin content of 0.202%.